2017
DOI: 10.19044/esj.2016.v13n2p269
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Aggression And Spiritual Well-Being Among The University Students In Jordan

Abstract: Background: University students have increased levels of depression and its complications. Aggression is a serious problem among the university students in Jordan, while spiritual well-being is associated with many psychosocial issues. The purpose of this study was to identify the relationship between depression, aggression, and spiritual well-being among the university students. Methods: A quantitative approach using crosssectional descriptive-correlation design was used to carry out on convenience sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Increased levels of Spirituality tend to evoke positive emotions and suspend the expression of anxiety and depression. Coping with existential stress and stress arising from the demands of daily living through Spirituality relieves feelings of hopelessness and empowers the individual as related research suggests (22,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of Spirituality tend to evoke positive emotions and suspend the expression of anxiety and depression. Coping with existential stress and stress arising from the demands of daily living through Spirituality relieves feelings of hopelessness and empowers the individual as related research suggests (22,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kibret and Tareke (2017), there is no significant relationship between year (batch) of students and psychological well-being measures. Additionally, Alorani and Alradaydeh (2017) found no significant differences in the mean scores of spiritual well-being based on students' educational year and specialty. However, according to Ziapour et al (2017), there is a significant relationship between academic term and field of study and spiritual well-being.…”
Section: Discussionmentioning
confidence: 68%
“…Ziapour, Khatony, Jafari, and Kianipour (2017) found that there are significant correlations among the demographic variables gender, marital status, age, housing, academic term, and field of study and spiritual well-being. Alorani and Alradaydeh (2017) identified the relationship between depression, aggression, and spiritual well-being among the university students. Results of their study showed a negative correlation between spiritual well-being and both of depression and aggression.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Spiritual well-being consists of two components of religious well-being and existential well-being. Religious well-being is a sign of communication with God, and existential well-being is the sense of purpose in life, peace, and life satisfaction [ 8 ]. Spiritual well-being had an effect on the physical, social, and psychological aspects of an individual's life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feizi et al found that healthcare students had moderate spiritual well-being and showed a positive correlation between happiness and spiritual well-being among healthcare students [ 11 ]. Moreover, Alorani and Alradaydeh demonstrated a negative correlation between spiritual well-being, depression, and aggression [ 8 ]. Fabbris et al indicated a significant association between well-being and reduced anxiety levels in nursing students [ 5 ].…”
Section: Introductionmentioning
confidence: 99%